Laser‐Induced Graphene on Paper toward Efficient Fabrication of Flexible, Planar Electrodes for Electrochemical Sensing. Issue 22 (24th October 2021) - Pinheiro, Tomás; Silvestre, Sara; Coelho, João; Marques, Ana C.; Martins, Rodrigo; Sales, M. Goreti F.; Fortunato, Elvira
Abstract: Laser irradiation to induce networks of graphene‐based structures toward cost‐effective, flexible device fabrication is a highly pursued area, with applications in various polymeric substrates. This work reports the application of this approach toward commonly available, eco‐friendly, low‐cost substrates, namely, chromatographic and office papers. Through an appropriate chemical treatment with sodium tetraborate as a fire‐retardant agent, photothermal conversion to porous laser‐induced graphene (LIG) on paper is achieved. Raman peaks are identified, with I 2D / I G and I D / I G peak ratios of 0.616 ± 0.095 and 1.281 ± 0.173, showing the formation of multilayered graphenic material, exhibiting sheet resistances as low as 56.0 Ω sq –1 . Coplanar, LIG‐based, three‐electrode systems (working, counter and reference electrodes) are produced and characterized, showing high current Faradaic oxidation and reduction peaks, translating in high electrochemical active area, doubling the geometric area. Good electron transfer kinetics performed exclusively with on‐chip measurements are reached, with k 0 values as high as 7.15 × 10 –4 cm s –1 . Proof‐of‐concept, amperometric, enzymatic glucose biosensors are developed, exhibiting good analytical performance in physiologically relevant glucose levels, with results pointing to the applicability of paper‐based LIG toward efficient, disposable electrochemical sensor development, increasing their sustainability and accessibility, while simplifying their production and reducing their cost. Abstract : The production of laser‐induced graphene from alternative and renewable origin, such as cellulose, can bring added value to common materials for their application in flexible bioelectronics. In this work, fire‐retardant chemical treatment is applied to common chromatography and office paper, granting the capability for laser‐induced graphene synthesis and optimization toward efficient fabrication of paper‐based, planar electrodes for electrochemical sensing.